Explaining the Appreciation of the Brazilian real - Mourougane, Annabelle (OECD Economics Department Working Papers, 2011)
This paper seeks to identify factors explaining the appreciation of the Brazilian real observed since 2003, which was temporarily interrupted only during episodes of financial turbulence. Net foreign assets and the productivity differential relative to Brazil's main trade partners are found to be significant determinants of the real effective exchange rate in the long run. In the short term, exchange-rate developments are mostly explained by movements in net foreign assets. The production of oil is also found to explain developments in the real effective exchange rate in the long run. These results are robust to a wide range of tests. There is evidence of an over-valuation of the real in 2010, but the extent of the misalignment is hard to gauge. FEER estimations point to an overvaluation between 3-10% in 2010. Dynamic simulations of behavioural exchange-rate equations generally suggest an overvaluation of between 10-20%. However, these estimations remain subject to large uncertainties